2020
DOI: 10.1021/acsomega.0c01067
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Oxidase Immobilized on Magnetic Zirconia: Controlling Catalytic Performance and Stability

Abstract: Here, we report the structures and properties of biocatalysts based on glucose oxidase (GOx) macromolecules immobilized on the mesoporous zirconia surface with or without magnetic iron oxide nanoparticles (IONPs) in zirconia pores. Properties of these biocatalysts were studied in oxidation of Dglucose to D-gluconic acid at a wide range of pH and temperatures. We demonstrate that the calcination temperature (300, 400, or 600 °C) of zirconia determines its structure, with crystalline materials obtained at 400 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 68 publications
2
11
0
Order By: Relevance
“…[ 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. To create an appreciable magnetic moment for a successful separation, magnetic NPs are often organized into clusters [ 34 , 38 ], imbedded in gels [ 36 ], other polymer or inorganic matrices [ 13 , 39 , 40 , 41 ], or self-assembled into larger structures [ 42 , 43 ]. This creates interparticle interactions and increases magnetic attraction between magnetic NPs and an external magnetic field.…”
Section: Magnetic Recovery As a Major Advantagementioning
confidence: 99%
See 4 more Smart Citations
“…[ 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. To create an appreciable magnetic moment for a successful separation, magnetic NPs are often organized into clusters [ 34 , 38 ], imbedded in gels [ 36 ], other polymer or inorganic matrices [ 13 , 39 , 40 , 41 ], or self-assembled into larger structures [ 42 , 43 ]. This creates interparticle interactions and increases magnetic attraction between magnetic NPs and an external magnetic field.…”
Section: Magnetic Recovery As a Major Advantagementioning
confidence: 99%
“…An especially fascinating enhancement of the enzyme activity was observed when both enzyme and iron oxide NPs were located in the vicinity of each other. The comparison of the activities of glucose oxidase (GOx) immobilized in porous silica (SiO 2 ), alumina (Al 2 O 3 ), and zirconia (ZrO 2 ), or in the same supports but containing magnetite NPs in the support pores (Fe 3 O 4 -SiO 2 , Fe 3 O 4 -Al 2 O 3 , Fe 3 O 4 -ZrO 2 ), revealed that biocatalysts based on magnetic supports are noticeably more active than those based on non-magnetic supports [ 13 , 41 ]. Figure 3 shows a trend for ZrO 2 and Fe 3 O 4 -ZrO 2 supports [ 41 ].…”
Section: Enhancement Of Enzymatic Activitymentioning
confidence: 99%
See 3 more Smart Citations